2015
DOI: 10.1371/journal.pone.0121061
|View full text |Cite
|
Sign up to set email alerts
|

“Mortui Vivos Docent” or Who Gives His Body to Science? The Analysis of the Personal Questionnaires of Polish Donors in the Conscious Body Donation Program

Abstract: The Conscious Body Donation Program conducted since 2003 by the Department of Human Anatomy, Medical University of Silesia in Katowice was the first innovative project aimed at obtaining informed donors' bodies for the purpose of teaching anatomy in Poland. The aim of this prospective study was to determine the declared donors' characteristics and to establish the possible motivation for body donation. A total of 244 application files were reviewed and the following information was analyzed: donor’s age, age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 21 publications
6
31
3
Order By: Relevance
“…In contrast to previous studies (Armstrong, ; Boulware et al, ; Rokade et al, ; Bajor et al, ), this study found no significant relationship between age and willingness towards body donation. This could be due to the limited age range among the participants of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies (Armstrong, ; Boulware et al, ; Rokade et al, ; Bajor et al, ), this study found no significant relationship between age and willingness towards body donation. This could be due to the limited age range among the participants of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Neuroanatomy students at UFJF appreciated the mixed strategy. This outcome encouraged teachers to maintain TBL sessions alternated with traditional lectures and practical classes, considering the relevance of anatomical specimen study and cadaver-based training throughout the world (Korf et al, 2008;Ahmed et al, 2010;da Rocha et al, 2013;Bajor et al, 2015;Habicht et al, 2018). However, it is important to encourage new studies which compare mixed strategies (i.e., TBL and lectures) and TBL as a single strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the demographic characteristics of actual body donors (Dluzen et al, ; Lagwinski et al, ; Labuschagne and Mathey, ; Anteby et al, ; Sadhu et al, ) and body donor registrants (Fennell and Jones, ; Bolt et al, ; McClea and Stringer, ; Cornwall et al, ; Bajor et al, ). The average age (70.5 years) and sex distribution (57% female) of registrants in this study is broadly congruent with previous New Zealand (Fennell and Jones, ; McClea and Stringer, ; Cornwall et al, ) studies during 1992, 2000–2009, and 2011, respectively, and overseas studies of registered body donors and actual donors from Ohio (US, data from 1978 to 1993; Dluzen et al, ; Lagwinski et al, ), Stellenbosch (South Africa, data from 1956 to 1996; Labuschagne and Mathey, ), Groningen (the Netherlands, data from 2000 to 2008; Bolt et al, ), Hawaii (US, data from 1967 to 2006; Anteby et al, ), Kolkata (India, data from 2001 to 2010; Sadhu et al, ), and Katowice (Poland, data timing unknown; Bajor et al, ). This supports the premise that registration for body donation frequently occurs in the sixth or seventh decade of life in many countries.…”
Section: Discussionmentioning
confidence: 99%